Women’s Language of Male Characters in Elemental Movie - Astari, Tjokorda Istri Agung Dyah; Aryawibawa, I Nyoman; Putra, Galuh Febri (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This undergraduate thesis is entitled "Women's Language of Male Characters in Elemental Movie". The study examines the features and functions of women's language used in the Elemental movie, which features a male lead character. The research is based on the framework proposed by Lakoff (2004) for understanding women's language features and the language function framework developed by Pearson (1985). The primary data for this study was collected through documentation and the note-taking method was used to analyze the data. Informal methods were used to present the analysis of the data, providing information on the frequency of women's language features used by male characters. This study is expected to contribute to the understanding of how women's language is used by male characters in movies, specifically in Elemental, and how it can be analyzed using different frameworks and methodologies. The result of this study found that there were four functions of women's language features used in this movie. In this thesis, the data from the Elemental movie has been analyzed to identify the features and functions of women's language. There are seven features found in the data including lexical hedges or fillers, empty adjectives, intensifiers, hypercorrect grammar, super polite forms of language, avoiding strong swear words, and emphatic stress. The characters in the movie use these features. The functions of these features are to express uncertainty, start a discussion, express feelings, and soften an utterance.